1998
DOI: 10.1051/agro:19980302
|View full text |Cite
|
Sign up to set email alerts
|

Root and shoot growth, water use and water use efficiency of spring durum wheat under early-season drought

Abstract: -One of the common features of the Mediterranean climate of North Africa is the uncertainty of rainfall immediately after durum wheat (Triticum durum Desf.) emergence, leading to early-season drought. Impacts of drought during wheat reproductive development have been thoroughly investigated, while studies of early-season drought are lacking. The objectives of the research reported here were to examine genotypic differences for some morphological traits in response to early-season drought, and to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Asseng et al (1998) reported that the maximum wheat root length was 30 km m -2 , which was similar to the results obtained in the current study (Table 3), and comparable values in the RLD (El-Hafi d et al, 1998;Steingrobe et al, 2001a) and root length (Merrill et al, 1996;Steingrobe et al, 2001b) were also reported. On the other hand, Oyanagi et al (1998) reported a shorter root length than that obtained in our study, especially in soybean.…”
Section: Root Growthsupporting
confidence: 91%
“…Asseng et al (1998) reported that the maximum wheat root length was 30 km m -2 , which was similar to the results obtained in the current study (Table 3), and comparable values in the RLD (El-Hafi d et al, 1998;Steingrobe et al, 2001a) and root length (Merrill et al, 1996;Steingrobe et al, 2001b) were also reported. On the other hand, Oyanagi et al (1998) reported a shorter root length than that obtained in our study, especially in soybean.…”
Section: Root Growthsupporting
confidence: 91%
“…Positive effects have been reported as a result of reducing soil evaporation, inhibition of weeds and the greater CO 2 fixation per unit of water transpired (e.g. LopezCastaneda et al, 1996;Elhafid et al, 1998;Rebetzke and Richards, 1999). Negative effects have been reported mainly due to early soil water depletion as a result of a greater canopy growth, where the crop is mainly dependent to stored soil water (e.g.…”
Section: Leaf Area Development Ratementioning
confidence: 99%
“…Some study reported that soil should has enough moisture content during the grouting stage, which not only can accelerate the transpiration rate and reduce plant body heat and canopy temperature of spring wheat, but also be benefit to improve the grouting rate and photosynthetic rate of spring wheat (Dong et al, 2001), The photosynthetic rate of spring-wheat in high soil moisture content is bigger obviously than low soil moisture content (Li et al, 2002), and under appropriate colony scale, increasing N supply be propitious to springwheat to absorb N and harmonize the metabolic equilibrium of plant N, which not only can improve the young spike differentiation and spike formation rate of spring-wheat in bearing prophase, but also can prevent the lamina premature senility and improve the photosynthetic rate in bearing anaphase and, heighten the transfer rate of dry matter from organ to seed, improve the spring wheat production , maintaining leaf area contributes to yield of spring wheat (Hafid et al, 1998), there was a significantly positive correlation between spring wheat yield and availability leaf area and leaf keeping time during the grouting stage (Zhao et al, 2005a,b), tiller and spike-formed rate determine the population construct and economic yield . All these physiological phenomena had appeared in our field experiment, the significance of yield under different treatments can be seen obviously.…”
Section: Interaction Analysismentioning
confidence: 99%